Clinical Management Strategies and Pregnancy Outcomes in Women with Mitral Valve Disease at Fetomaternal Medicine Department, BMU (University Heart Journal, 2025)
Background: Mitral valve disease complicating pregnancy poses substantial clinical challenges due to altered maternal cardiovascular physiology and is associated with increased risks to both mother and fetus. This study evaluates the demographic profile, clinical presentation, management approaches, and maternal– fetal outcomes of pregnant women diagnosed with mitral valve disease at the Department of Fetomaternal Medicine, Bangladesh Medical University.Methods: This observational study enrolled 60 pregnant women with confirmed mitral valve disease who received care at the Fetomaternal Medicine Department of Bangladesh Medical University between July 2023 and June 2024. Serial clinical evaluations and echocardiographic examinations were conducted throughout pregnancy. Management followed established institutional protocols with close surveillance of maternal cardiac status and fetal health. Primary endpoints included maternal cardiac events, obstetric complications, and fetal/neonatal outcomes.Results: The mean maternal age was 27.3 ± 4.8 years. Rheumatic heart disease accounted for the majority of cases (85%). At initial assessment, 45% of patients were classified as NYHA functional class I, 35% as class II, and 20% as class III or IV. Maternal cardiac complications were documented in 23.3% of patients, most commonly heart failure (13.3%). Vaginal delivery occurred in 58.3% of pregnancies. Unfavorable fetal outcomes were noted in 26.7% of cases, including preterm birth (20%) and low birth weight (23.3%). Conservative medical treatment was effective in 88.2% of patients. Multivariate regression analysis demonstrated that NYHA class III/IV (OR 3.8, 95% CI 1.8–7.9), mitral valve area < 1.5 cm² (OR 2.9, 95% CI 1.4–6.2), and pulmonary hypertension (OR 2.6, 95% CI 1.2–5.5) independently predicted adverse outcomes.Conclusion: Appropriate risk stratification, vigilant monitoring, and tailored management can result in satisfactory maternal and fetal outcomes among pregnant women with mitral valve disease. Identification of high-risk features allows informed clinical decision-making, particularly in low-resource settings.University Heart Journal 2025; 21(2): 81-86